Hippocampal TET1 and TET2 Expression and DNA Hydroxymethylation Are Affected by Physical Exercise in Aged Mice - Jessop, Peter; Toledo-Rodriguez, Maria (Frontiers in Cell and Developmental Biology, 2018)
The function of 5-hydroxymethylcytosine (5hmC) is poorly understood. 5hmC is an epigenetic modification of DNA, resulting from the oxidation of 5-methylcytosine (5mC) by the Fe2+ and 2-oxoglutarate-dependent, ten-eleven translocation methylcytosine dioxygenases (TET1, TET2 and TET3). Recent evidence suggests that, in addition to being an intermediate in active demethylation, 5hmC may also have an epigenetic role. 5hmC is enriched in the adult brain, where it has been implicated in regulating neurogenesis. The rate of adult neurogenesis decreases with age, however physical exercise has been shown to counteract this deficit. Here we investigated the impact of voluntary exercise on the age-related changes of TET1, TET2 expression and 5hmC content in the hippocampus and hypothalamus. For this purpose, we used voluntary exercise in young adult (3 months) and aged (18 months) mice as a rodent model of healthy brain aging. We measured the levels of hippocampal and hypothalamic TET1, TET2 mRNA and 5hmC and memory (Object Location test) in mice that either exercised for 1 month or remained sedentary. While aging was associated with decreased TET1 and TET2 expression, voluntary exercise counteracted the decline in expression. Moreover, aged mice that exercised had higher hippocampal 5hmC content in the promoter region of miR-137, an miRNA involved in adult neurogenesis. Exercise improved memory in aged mice, and there was a positive correlation between 5hmC miR-137 levels and performance in the Object Location test. In the hypothalamus neither exercise nor aging affected TET1 or TET2 expression. These results suggest that exercise partially restores the age-related decrease in hippocampal TET1 & TET2 expression, which may be linked to the improvement in memory. Future studies should further determine the specific genes where changes in 5hmC levels may mediate the exercise-induced improvements in memory and neurogenesis in aged animals.